Chemoradiotherapy Is Superior to Radiotherapy Alone in Esophageal Cancer Patients Older Than 65 Years: A Propensity Score-Matched Analysis of the SEER Database - Xia, Xiaojie; Gao, Qing; Ge, Xiaolin; Liu, Zeyuan; Di, Xiaoke; Sun, Xinchen; Yang, Yan (Frontiers in Oncology, 2021)
Introduction Radiotherapy (RT) is the main treatment for unoperated esophageal cancer (EC) patients. It is controversial whether adding chemotherapy (CT) to RT is beneficial for elderly EC patients. The purpose of our study was to compare the efficacy of chemoradiotherapy (CRT) with RT alone for non-surgical elderly esophageal cancer patients. Methods A total of 7,101 eligible EC patients older than 65 years diagnosed between 2000 and 2018 were collected from the Surveillance, Epidemiology, and End Results (SEER) database. All the samples were divided into the radiotherapy group and the chemoradiotherapy group. After being matched by propensity score matching (PSM) at a 1:1 ratio, 3,020 patients were included in our analysis. The Kaplan–Meier method and log-rank test were applied to compare overall survival (OS) and cancer-specific survival (CSS). Results After PSM, the clinical characteristics of patients between the RT and CRT groups were comparable. For EC patients older than 65 years, the 3-year OS and CSS in the CRT group were 21.8% and 27.4%, and the 5-year OS and CSS in the CRT group were 12.7% and 19.8%, respectively. The 3-year OS and CSS in the RT group were 6.4% and 10.4%, and the 5-year OS and CSS in the RT group were 3.5% and 7.2%, respectively. Next, these patients were divided into five subgroups based on the age stratification (ages 65–69; 70–74; 75–79; 80–84; ≥85). In each subgroup analysis, the 3- and 5-year OS and CSS showed significant benefits in the CRT group rather than in the RT group (all p < 0.05). We were unable to assess toxicities between the two groups due to a lack of correlated information. Conclusions CRT could improve OS and CSS for non-surgical EC patients older than 65 years. Adding chemotherapy to radiation showed a significant prognostic advantage for elderly esophageal cancer patients.